Urgency of Arabic in Islamic Education - Dian Ekawati (Postgraduate of IAIN Metro Lampung Indonesia, 2019)
Language is a tool of communication and Arabic has been used as this tool in the international conversation. Arabic is rapidly developing throughout the world and has been studied both formally and informally at educational institutions. Learning Arabic requires carefulness and seriousness since to the tool of science obtained in Arabic will not be easily understood in such a short time of learning. The holy book of Islam is the Qur'an written in Arabic. Therefore, who wants to understand Islam properly are strongly recommended to learn Arabic seriously as the least possible thing can he do. That is because by studying Arabic, he will be able to understand every meaning of Islamic teachings that contained in the holy Qur'an which has been written in Arabic. The Qur'an and hadith are the main sources of the implementation of Islamic teachings, Thus, if Muslims understand Arabic pretty well then understanding both the Qur'an and hadith will surely be easier and can also prevent them from misunderstanding or misinterpreting the content. Therefore, in Islamic education, Arabic education is very important to be taught. Arabic is not merely the language of Moslems but the language that Allah has choosen as the language of Qur'an. The urgency of learning Arabic is very important in Islamic education in order to be able to understand to the teachings contained in Islamic education.